Itaconate and fumarate derivatives inhibit priming and activation of the canonical NLRP3 inflammasome in macrophages. Issue 4 (2nd March 2022) - Hoyle, Christopher; Green, Jack P.; Allan, Stuart M.; Brough, David; Lemarchand, Eloise
Abstract: The NLRP3 inflammasome is a multiprotein complex that regulates caspase‐1 activation and subsequent interleukin (IL)‐1β and IL‐18 release from innate immune cells in response to infection or injury. Derivatives of the metabolites itaconate and fumarate, dimethyl itaconate (DMI), 4‐octyl itaconate (4OI) and dimethyl fumarate (DMF) limit both expression and release of IL‐1β following NLRP3 inflammasome activation. However, the direct effects of these metabolite derivatives on NLRP3 inflammasome responses require further investigation. Using murine bone marrow‐derived macrophages, mixed glia and organotypic hippocampal slice cultures (OHSCs), we demonstrate that DMI, 4OI and DMF pretreatments inhibit pro‐inflammatory cytokine production in response to lipopolysaccharide (LPS), as well as inhibit subsequent NLRP3 inflammasome activation induced by nigericin. DMI, 4OI, DMF and monomethyl fumarate (MMF), another fumarate derivative, also directly inhibited biochemical markers of NLRP3 activation in LPS‐primed macrophages, mixed glia, OHSCs and human macrophages in response to nigericin and imiquimod, including ASC speck formation, caspase‐1 activation, gasdermin D cleavage and IL‐1β release. DMF, an approved treatment of multiple sclerosis, as well as DMI, 4OI and MMF, inhibited NLRP3 activation in macrophages in response to lysophosphatidylcholine, which is used to induce demyelination, suggesting a possible mechanism for DMF in multiple sclerosis through NLRP3 inhibition. The derivatives also reduced pro‐IL‐1α cleavage in response to the calcium ionophore ionomycin. Together, these findings reveal the immunometabolic regulation of both the priming and activation steps of NLRP3 activation in macrophages. Furthermore, we highlight itaconate and fumarate derivatives as potential therapeutic options in NLRP3‐ and IL‐1α‐driven diseases, including in the brain. Abstract : The effects of itaconate and fumarate derivatives on canonical NLRP3 inflammasome activation in macrophages and microglia were investigated. Itaconate and fumarate derivatives inhibited both the priming and activation steps of canonical NLRP3 activation in response to nigericin, imiquimod and lysophosphatidylcholine stimulation. The derivatives also reduced interleukin‐1α cleavage in response to ionomycin.